The Importance of Unprotected Areas as Habitat for The Leopard Cat (Prionailurus bengalensis javanensis Desmarest, 1816) on Java, Indonesia - Nanang Irawan; Satyawan Pudyatmoko; Pujo Semedi Hargo Yuwono; Muhammad Tafrichan; Anthony J. Giordano; Muhammad Ali Imron (Jurnal Ilmu Kehutanan)
Protected areas play important roles for protecting many endangered species in Indonesia. However, very limited information regarding roles of protected areas and non-protected areas for supporting the habitat of less-concerned carnivores in Java, leopard cat (Prionailurus bengalensis javanensis). We aim to assess the relative roles of non-protected areas for the habitat of this cat on the highly fragmented and populated island of Java. We develop species distribution modelling, using Maxent by integrating various sources of presence data of this species and environmental data. Our finding confirms that leopard cat can life in various habitat types but mainly patchy forest areas. While most of the protected areas are suitable for the habitat of this smallest cat on Java, the non-protected areas provide much larger areas for its habitat (66.8 %). Our findings highlighted the importance of maintaining connectivity among habitat patches in non-protected areas, habitat protection using current government policy on high conservation value forest and essential ecosystems areas.